UMPSA strengthens commitment in Strengthening Phase of Malay Language Empowerment Plan as Language of Knowledge at Public Universities - Hamizah, Zahari; Nik Aloesnita, Nik Mohd Alwi (UMPSA, 2025)
SHAH ALAM, 23 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to support the national agenda of empowering the Malay language as the language of knowledge by participating in the Reporting Workshop on the Malay Language Empowerment Plan in Public Institutions of Higher Learning (IPTA) 2025–2030 held on 22 and 23 May 2025 at Concorde Hotel, Shah Alam.